Reticulon‐like properties of a plant virus‐encoded movement protein. Issue 2 (29th September 2020) - Lazareva, Ekaterina A.; Lezzhov, Alexander A.; Chergintsev, Denis A.; Golyshev, Sergei A.; Dolja, Valerian V.; Morozov, Sergey Y.; Heinlein, Manfred; Solovyev, Andrey G.
Summary: Plant viruses encode movement proteins (MPs) that ensure the transport of viral genomes through plasmodesmata (PD) and use cell endomembranes, mostly the endoplasmic reticulum (ER), for delivery of viral genomes to PD and formation of PD‐anchored virus replication compartments. Here, we demonstrate that the Hibiscus green spot virus BMB2 MP, an integral ER protein, induces constrictions of ER tubules, decreases the mobility of ER luminal content, and exhibits an affinity to highly curved membranes. These properties are similar to those described for reticulons, cellular proteins that induce membrane curvature to shape the ER tubules. Similar to reticulons, BMB2 adopts a W‐like topology within the ER membrane. BMB2 targets PD and increases their size exclusion limit, and these BMB2 activities correlate with the ability to induce constrictions of ER tubules. We propose that the induction of ER constrictions contributes to the BMB2‐dependent increase in PD permeability and formation of the PD‐associated replication compartments, therefore facilitating the virus intercellular spread. Furthermore, we show that the ER tubule constrictions also occur in cells expressing TGB2, one of the three MPs of Potato virus X (PVX), and in PVX‐infected cells, suggesting that reticulon‐like MPs are employed by diverse RNA viruses.